2006
DOI: 10.1161/01.hyp.0000236119.96301.f2
|View full text |Cite
|
Sign up to set email alerts
|

The Valsartan Antihypertensive Long-Term Use Evaluation (VALUE) Trial

Abstract: Abstract-In the main Valsartan Antihypertensive Long-Term Use Evaluation (VALUE) report, we investigated outcomes in 15 245 high-risk hypertensive subjects treated with valsartan-or amlodipine-based regimens. In this report, we analyzed outcomes in 7080 patients (46.4%) who, at the end of the initial drug adjustment period (6 months), remained on monotherapy. Baseline characteristics were similar in the valsartan (Nϭ3263) and amlodipine (Nϭ3817) groups. Time on monotherapy was 3.2 years (78% of treatment expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 19 publications
3
75
0
13
Order By: Relevance
“…2). Increased activity of the renin angiotensin system has been associated with obesity and glucose intolerance, and prospective epidemiological studies have reported that blocking the system using either ACE inhibitors or ARBs has been shown to reduce the incidence of diabetes (27,28,29,30) and both ACE-inhibitors and ARBs may improve insulin action to different extents (31,32) as well as insulin secretion (33). Accordingly, it may be considered biologically plausible that bioactive peptides in the Cardi04 yogurt inhibiting ACE may reduce plasma glucose levels in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…2). Increased activity of the renin angiotensin system has been associated with obesity and glucose intolerance, and prospective epidemiological studies have reported that blocking the system using either ACE inhibitors or ARBs has been shown to reduce the incidence of diabetes (27,28,29,30) and both ACE-inhibitors and ARBs may improve insulin action to different extents (31,32) as well as insulin secretion (33). Accordingly, it may be considered biologically plausible that bioactive peptides in the Cardi04 yogurt inhibiting ACE may reduce plasma glucose levels in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…If we adjust the prevalence according to age, we see that 75 % of hypertensive women and 65 % of hypertensive men are aged [60 years [19] and that three of every four patients with known cardiovascular disease have hypertension [20]. Studies [21,22] indicate that clinical inertia can have an adverse impact on clinical outcomes because hypertensive patients need early BP control and any delay is associated with an increased incidence of cardiovascular events. Long-term follow-up studies are needed to measure the impact of clinical inertia on clinical outcomes in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, to determine the potential role of AII in vascular endothelial injury, we compared the effect of valsartan and amlodipine on vascular injury of DS rats (Figures 1 and 2 and supplemental Figures I and II). Recent report by Julius et al 23 on subanalysis of the Valsartan Antihypertensive Long-Term Use Evaluation (VALUE) trial has indicated that valsartan is superior to amlodipine in terms of the prevention of hypertensive heart failure, although its mechanism remains to be clarified. Therefore, our present study, comparing between valsartan and amlodipine in DS rats, is of clinical relevance.…”
Section: Discussionmentioning
confidence: 99%